Improved determination of marine sedimentation rates using Th-230(xs) - Bourne, M; Thomas, A; Mac Niocaill, C; Henderson, G (John Wiley and Sons, 2012)
[1]Measurements of excess 230Th (230Thxs) have proved to be a useful tool in constraining changes in sedimentation rate, and improving our understanding of the fluxes of other components into marine sediments. To obtain the initial activity of 230Thxs (230Thxs0) in sediment: the total measured 230Th must be corrected for the presence of 230Th associated with detrital minerals, for ingrowth from uranium-bearing authigenic phases and then also corrected for the decay of 230Thxs since deposition. We describe a number of improvements in the way these corrections are applied to obtain more accurate determinations of 230Thxs0. We present a new method for the determination of a local estimate for the detrital 238U/232Th activity ratio; suggest more appropriate values for the isotopic composition of authigenic uranium; and question the assumption of secular equilibrium in detrital material. We also present a new, freely-available MATLAB® script called ‘XSage’ that can calculate 230Thxs0, from user-supplied datasets of uranium and thorium isotope activities from sedimentary samples following the theoretical approach described. ‘XSage’ can determine variations in sedimentation rate between stratigraphic horizons of known age and thus produce high-resolution age models. Using a Monte Carlo approach, the program calculates uncertainties for these age models and on the durations of intervals between tie-points. An example of the application of the XSage program using a previously published record is provided.